Alcoholic Beverages Distribution in Indonesia: A Socio-Legal Analysis under Criminal and Food Law - Wicaksono, Genta Yuris; Putri, Hanuring Ayu Ardhani; Suniaprily, Firstnandiar Glica Aini (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study analyzes the legal provisions and practices surrounding the distribution of Alcoholic Beverages (Ciu) in Bekonang Village through empirical juridical analysis. The results show that although regulations such as Law No. 18 of 2012 concerning Food and Article 204 of the Criminal Code have established a normative legal framework, there is a wide gap with the reality on the ground (law in action). Ciu remains widely circulated because it has become integrated as a tradition and a source of community income, thus gaining strong social legitimacy. Repressive law enforcement faces complex dilemmas and obstacles due to socio-cultural and economic factors. Efforts by authorities tend to be incidental and fail to address the root of the problem. Therefore, a solely criminal law approach is deemed ineffective and unsustainable. This study concludes that a more comprehensive and integrative policy is needed. The solution lies in reinterpreting regulations that take into account the characteristics of traditional beverages, supported by socio-legal strategies such as health education, business development, and strengthened operational oversight by local governments. Ultimately, a sustainable solution must be able to reconcile formal legal certainty with local wisdom and community economic well-being.